A STUDY ON SPEAKING STRATEGIES USED BY ENGLISH STUDY PROGRAM STUDENTS OF FKIP UNIVERSITAS RIAU - Zhazha Zalma Cahyani; Erni Erni; Masyhur Masyhur (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2023)
Abstract: Speaking is communication occurs when the listener can provide the speaker's response after the listener understands the message conveyed. The objective of this descriptive research was to describe the students’ Speaking Strategies Used by English Study Program, Universitas Riau. The population of this research was the fourth year students of English study program of FKIP Universitas Riau of 2022/2023 academic year. The whole number of the population is about 119 students. Due to the large population which is consisting of 3 classes, the cluster random sampling technique is used. One of the classes is taken as the sample as many as 39 students. This research design used descriptive-quantitative method as the research data approach. There were 20 items in the questionnaire. The adopted from SILL questionnaire (Strategy Inventory for Language Learning) version 7.0 is used to collect the data. The questionnaire were collected through Google Form. The collected data were analyzed by using Microsoft excel. The findings of this study revealed that the student tent to use social strategies with average score of 3.90 (classified as high level), In short, it can be inferred that the students’ strategy in speaking English is mostly used is a social strategy. It was very important to practice every day with lowering his anxiety and more cooperating with himself. The suggestion is it would be better if they also can use the other strategies which are appropriate to their tasks, difficulties and learning objectives. Then, hopefully students can improve their English by using more language learning strategies in their learning to help learning easier, and enjoyable.Key Words: Speaking, Language Learning Strategies, English Study Program